Chromosomal organization and evolutionary history of Mariner transposable elements in Scarabaeinae coleopterans - Oliveira, Sarah G. [UNESP]; Cabral-de-Mello, Diogo C. [UNESP]; Moura, Rita C.; Martins, Cesar [UNESP] (Biomed Central Ltd., 2013)
Background: With the aim to increase the knowledge on the evolution of coleopteran genomes, we investigated through cytogenetics and nucleotide sequence analysis Mariner transposons in three Scarabaeinae species (Coprophanaeus cyanescens, C. ensifer and Diabroctis mimas).Results: The cytogenetic mapping revealed an accumulation of Mariner transposon in the pericentromeric repetitive regions characterized as rich in heterochromatin and C(0)t-1 DNA fraction (DNA enriched with high and moderately repeated sequences). Nucleotide sequence analysis of Mariner revealed the presence of two major groups of Mariner copies in the three investigated coleoptera species.Conclusions: The Mariner is accumulated in the centromeric area of the coleopteran chromosomes probably as a consequence of the absence of recombination in the heterochromatic regions. Our analysis detected high diversification of Mariner sequences during the evolutionary history of the group. Furthermore, comparisons between the coleopterans sequences with other insects and mammals, suggest that the horizontal transfer (HT) could have acted in the spreading of the Mariner in diverse non-related animal groups.
Keywords: Chromosomal rearrangements; Evolution; Heterochromatin; Horizontal transfer; Repetitive DNA; Transposition